Work life balance and transformational leadership as predictors of employee job satisfaction - George, Priya; Sreedharan, Narappichi Veetil (Serbian Journal of Management, 2023)
The main aim of the present study is to examine the relationship between work life balance, transformational leadership and job satisfaction of employees among information technology (IT) employees in South India. There are very limited number of studies that have focussed on the effects of work life balance and transformational leadership on job satisfaction among IT employees. The data for the study was collected using structured questionnaires from 250 employees working in the Indian IT sector.  Statistical Package for Social Sciences (SPSS) application was used to conduct reliability, descriptive, correlation and regression analyses on the collected data. The findings suggested that transformational leadership and work life balance have a positive and significant effect on an employee’s job satisfaction. The study recommends strategies for increasing employee satisfaction by formulating policies to ensure work-life balance and encourages IT organisations to provide transformational leadership training for managers to improve transformational leadership skills, such as maintaining good employee relationships by supporting employees in professional and personal matters.  This article examines the concept of transformational leadership in its totality; however, additional research is necessary to determine the effects of various dimensions of transformational leadership on employee job satisfaction.
Keywords: Information Technology; Job Satisfaction; Transformational Leadership; Work Life Balance